Axin phosphorylation in both Wnt-off and Wnt-on states requires the tumor suppressor APC. - Ofelia Tacchelly-Benites; Zhenghan Wang; Eungi Yang; Hassina Benchabane; Ai Tian; Michael P Randall; Yashi Ahmed (PLoS Genetics, 2018)
The aberrant activation of Wnt signal transduction initiates the development of 90% of colorectal cancers, the majority of which arise from inactivation of the tumor suppressor Adenomatous polyposis coli (APC). In the classical model for Wnt signaling, the primary role of APC is to act, together with the concentration-limiting scaffold protein Axin, in a "destruction complex" that directs the phosphorylation and consequent proteasomal degradation of the transcriptional activator β-catenin, thereby preventing signaling in the Wnt-off state. Following Wnt stimulation, Axin is recruited to a multiprotein "signalosome" required for pathway activation. Whereas it is well-documented that APC is essential in the destruction complex, APC's role in this complex remains elusive. Here, we demonstrate in Drosophila that Axin exists in two distinct phosphorylation states in Wnt-off and Wnt-on conditions, respectively, that underlie its roles in the destruction complex and signalosome. These two Axin phosphorylation states are catalyzed by glycogen synthase kinase 3 (GSK3), and unexpectedly, completely dependent on APC in both unstimulated and Wnt-stimulated conditions. In a major revision of the classical model, we show that APC is essential not only in the destruction complex, but also for the rapid transition in Axin that occurs after Wnt stimulation and Axin's subsequent association with the Wnt co-receptor LRP6/Arrow, one of the earliest steps in pathway activation. We propose that this novel requirement for APC in Axin regulation through phosphorylation both prevents signaling in the Wnt-off state and promotes signaling immediately following Wnt stimulation.